RADECE (Reading, Answer, Discuss, Create and Evaluation): E-Learning Model “Merdeka Belajar” through Higher of Think of Al-Islam and Kemuhammadiyahan - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
The aim of this article is Radec (reading, answer, discuss and create): E-Learning Model through higher of think of Al-Islam and Kemuhamamdiyahan. The method of the research is qualitative method. A two-part questionnaire served as the study tool of Al-Islam and Muhammadiyahan. The first portion of the questionnaire was administered before to the activity and was designed to show the teachers' experience with implementing currently popular innovative learning methods of Al-Islam and Muhammadiyahan. After the session, the teachers were given a second part questionnaire to determine their readiness to adopt the RADEC learning paradigm. The data was analyzed both quantitatively and qualitatively. According to the findings of the first questionnaire, teachers have been unable to integrate currently popular creative learning methods due to a variety of factors of Al-Islam and Muhammadiyahan. According to the findings of the first questionnaire, teachers have been unable to integrate currently popular creative learning methods due to a variety of factors. The second study's findings suggest that socialization and workshops can help teachers use the RADEC learning approach. The majority of individuals who say that the syntax of the RADECE learning model through higher of think of Al-Islam and Kemuhammadiyahan demonstrate this. They are interested in researching the implementation of the RADECE learning model through higher of think of Al-Islam and Kemuhammadiya; and they are interested in researching the implementation of the RADECE learning model through higher of think of Al-Islam and Kemuhammadiya; and they are interested in researching the implementation of the RADECE learning model through higher of think of Al-Islam and Kemuhammadiyah.